Antibacterial activity of temu kunci tuber (kaempheria pandurata) essential oil against Bacillus cereus (Medical Journal of Indonesia, 2009)
Aim The mechanism of temu kunci tuber essential oil potential as antimicrobial agent has not been reported. To analyze the mechanism of antibacterial activity of temu kunci tuber essential oil from Yogyakarta on B.cereus. Antibacterial activity of essential oil were analyzed for its ability to disrupt bacterial cell membrane, that caused cell leakage and altered the morphology of the bacteria. Leakage was measured by analyzing the Ca+2, K+ ion outflow using an atomic adsorption spectrometry (AAS), and protein and nucleic acid using an ultraviolet spectrophotometer (UVS) on 280 nm and 260 nm respectively. Alterations in morphology were assessed using scanning electron microscopy (SEM). Results Minimum inhibitory concentration (MIC) of temu kunci essential oil on B.cereus was 0.12% (v/v). Treatment of B. cereus using 1MIC and 2MIC showed significant leakage compared to control (P<0.05). The K+ and Ca+2 ion leakage from the bacterial cells were between 10.32-35.57% and 15.05-41.54% respectively and showed significant difference compared to control (P<0.05). The absorbance observed by UVS for protein and nucleic acid leakage were 0.6330-0.8670 at 280 nm and 0.4320-0.8307 at 260 nm, respectively, and were significantly different compared to control (P<0.05). Exposure of 1 MIC temu kunci essential oil on B.cereus caused thickening as well as irregularities on the cell wall. At 2 MIC cells seemed transparent, empty looking and showed a ghost-like appearance. Conclusion Kaempheria pondurata essential oil could cause leakage and alter the morphology of the bacteria. (Med J Indones 2009; 18:10-7) Keywords: leakage, morphology